The Constitution as a Living Constitution: Dynamic S of Interpretation in The Indonesia Legal System - Syaidi, Ridwan (Law and Economics, 2025)
The problem of interpretation of the Indonesian constitution faces a dilemma between normative stability and adaptation to contemporary socio-political dynamics. This study aims to examine the operationalization of the living constitution in the practice of the constitutional judiciary, analyze the hermeneutic methodology of the Constitutional Court, and evaluate the impact of evolutionary interpretation on the constitutional system. Through a qualitative approach based on literature research with doctrinal analysis, the study revealed that the Constitutional Court has implemented the living constitution paradigm through a synthesis of multidimensional interpretations that integrate literal, contextual, and purposive dimensions. The metamorphosis of the role from negative legislator to positive legislator shows the adaptive elasticity of institutions in the face of today's legal complexity. The doctrine of universality of rights becomes an epistemological foundation that allows for the expansion of fundamental protections beyond the explicit enumeration of the constitution. Pancasila-based constitutional identity actualizes the synthetic harmony between tradition and modern constitutionalism. Despite the threat of democratic decline, the living constitution shows strategic potential as an instrument of constitutional consolidation whose effectiveness depends on the preservation of judicial independence and the commitment to the rule of law.